2007
DOI: 10.1111/j.1349-7006.2007.00486.x
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin inhibits the growth and peritoneal metastasis of gastric cancer through its specific membrane receptors AdipoR1 and AdipoR2

Abstract: Adiponectin, a circulating peptide hormone produced in adipose tissue, has been shown to be reduced in the plasma of patients with cancer, suggesting that this adipokine may be mechanically involved in the pathogenesis of adiposity-related carcinogenesis. In this study, we examined the expression of adiponectin receptors (AdipoR1 and AdipoR2) and assessed the function of adiponectin in gastric cancer. All of the six gastric cancer cell lines significantly expressed mRNA and protein of both receptors with varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
95
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(101 citation statements)
references
References 63 publications
5
95
0
1
Order By: Relevance
“…The mechanisms are not clear yet and require further investigation. However, recent studies have provided evidence that adipose tissue can produce many cytokines (adipokines), such as leptin and adiponectin, which can potently affect the biological behavior of malignant cells [41][42][43][44][45][46][47][48][49][50]. Our data support the hypothesis that these adipose tissue-derived factors are differently associated with the caricinogenesis or progression of GC of each histological type.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The mechanisms are not clear yet and require further investigation. However, recent studies have provided evidence that adipose tissue can produce many cytokines (adipokines), such as leptin and adiponectin, which can potently affect the biological behavior of malignant cells [41][42][43][44][45][46][47][48][49][50]. Our data support the hypothesis that these adipose tissue-derived factors are differently associated with the caricinogenesis or progression of GC of each histological type.…”
Section: Discussionsupporting
confidence: 80%
“…Recent studies have demonstrated that adipocytes produce a variety of secretory peptides, named adipokines [39,40]. More recently, some adipokines, such as leptin and adiponectin, have been shown to critically regulate the biological behavior of malignant cells [41][42][43][44][45][46][47][48][49][50], raising the possibility that adipocytes may have positive roles in the development of malignant diseases through the secretion of adipokines in an endocrine or intracrine manner. In addition, it has been suggested that the biochemical characteristics of visceral and subcutaneous adipose tissues are somewhat different [51,52].…”
Section: Introductionmentioning
confidence: 99%
“…However our AdipoR1 RNA interference data suggest that the effects demonstrated here are mediated via the specific AdipoR1 receptor. One study has shown that both AdipoR1 and AdipoR2 were required for the inhibition of cell proliferation by adiponectin in AZ521 and HGC27 gastric cancer cells, but that study did not explore the intracellular mechanisms responsible and used full length adiponectin at a much higher, supraphysiological concentration of 30 g /ml to inhibit epidermal-growth factor driven proliferation (Ishikawa et al 2007). Further recent studies have shown that full length adiponectin (the only form tested) inhibited the growth of MCF7 breast cancer cells, these cells expressed both AdipoR1 and AdipoR2, but the specific involvement of each receptor isoform was not investigated (Dieudonne et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The higher expression of AdipoR1, the stronger growth inhibitory effect of adiponectin was observed in cancer cell lines (Tsukada et al, 2011). A down-regulation of AdipoR1 by specific siRNA could also significantly suppress the antiproliferative effects of adiponectin (Ishikawa et al, 2007). Although the functional of adiponectin receptors in cancer cells has not been fully explained, the AMP-activated protein kinase (AMPK) may play an important role in the limits of cancer cell lines proliferation by adiponectin and its receptors (Kim et al, 2010).…”
Section: Introductionmentioning
confidence: 99%